Decreased Warfarin Clearance with the CYP2C9 R150H (*8) Polymorphism - Liu, Yong (2012)
The cytochrome P450 (CYP) 2C9 R150H (*8) allele occurs commonly in African Americans and is associated with lower warfarin dose requirements. We examined whether the CYP2C9*8 allele impacts warfarin clearance through a pharmacokinetic study in warfarin-treated African American patients and an in vitro kinetic study of S-warfarin 7-hydroxylation using cDNA-expressed CYP2C9 enzymes. We observed a 30% reduction in the unbound oral clearance of S-warfarin and 25% lower R- to S-warfarin plasma concentration in patients with the CYP2C9*8 allele (n=12) compared to CYP2C9*1 homozygotes (n=26). Consistent with these findings, the in-vitro intrinsic clearance of S-warfarin was 30% lower with the cDNA-expressed R150H protein compared to the wild-type protein. These data show that the R150H variant of the CYP2C9*8 allele reduces S-warfarin clearance, thus providing clinical and experimental evidence to explain lower warfarin dose requirements with the CYP2C9*8 allele.